Inventory Of Cultural Heritage In Pematangsiantar City Become A Learning Media Of The Colonial Era - Satria Chandra (Journal Analytica Islamica, 2024)
The city of Pematangsiantar is one of many hidden historical gems in Indonesia, preserving various eras in its historical buildings and Dutch colonial artifacts. This research aims to appreciate and utilize this cultural heritage as an educational tool, focusing on the inventory of cultural heritage in the city of Pematangsiantar. The Cultural Heritage Expert Team plays a crucial role in recommending cultural heritage objects, while the local government, especially the Department of Education and Culture, plays a role in preserving this heritage. Through strategic initiatives such as the Regional Cultural Thought Document and the Village Cultural Advancement Program, Pematangsiantar shows a strong commitment to cultural preservation.nThe younger generation, led by the Simalungun Museum Foundation, plays a significant role in preserving and disseminating cultural heritage, from renovating historical buildings to digital campaigns and seminars. In the context of the Merdeka Curriculum, learning modules designed to study colonial history provide a contextual and relevant foundation for students. With a deep qualitative approach, this research explores the complexity of Pematangsiantar's cultural heritage and gains valuable insights from the various parties involved. The research results show proactive efforts in preserving cultural heritage, with the hope that this heritage is not only preserved but also celebrated. Through strong collaboration between researchers, the government, and the community, Pematangsiantar sets high standards in cultural preservation and local history education, becoming a model for other cities in Indonesia.